PERUBAHAN PENGGUNAAN LAHAN DI KESATUAN HIDROLOGIS GAMBUT SUNGAI MALUKA – SUNGAI MARTAPURA - Budimansyah, Budimansyah; Kissinger, Kissinger; Fatmawati, Fatmawati; Kadir, Syarifuddin (Universitas Lambung Mangkurat, 2023)
Land use change is a dynamic process caused by human activities, and this change will have an impact on the hydrological response in a Peatland Hydrological Unit (KHG). The purpose of this study was to determine land use changes that occurred in the Maluka River KHG - Martapura River. Land use change analysis was conducted using an overlay method from the results of image analysis using satellite imagery data on Google Earth Pro. The on-screen digitization method was used to see land use between 2012 and 2022. The results showed that land use change in the Maluka River - Martapura River KHG in the period 2012 - 2022 with an area of 4,329.90 Ha or 4.8% of the total area of KHG. While 86,410.50 Ha or 95.2% did not experience land use change. The growth of land use for settlements and places of activity has experienced an additional trend, this also occurs in land use for ponds, plantations, mining, ponds, and moor/fields. Meanwhile, there is land subsidence in the forest, mangrove, swamp, rice field, shrub, and open land sectors, which can affect the balance of the ecosystem.